2016
DOI: 10.1080/10773525.2016.1187476
|View full text |Cite
|
Sign up to set email alerts
|

The power of local action in occupational health: the adoption of local exhaust ventilation in the Chicago tuckpointing trade

Abstract: Background: Silica is a pervasive and potentially deadly occupational hazard in construction. The occupational risk posed by silica has long been known, but efforts to use engineering controls to minimize dust generation in tuckpointing operations, a masonry restoration specialty, have been slow. Objectives: The objective of this study is to explore how local innovation in occupational safety and health may emerge, absent the establishment of national standards. Method:This study uses a case study to explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A systematic review by Robson et al (2010), found that workplace training was effective in increasing worker knowledge of hazards and in development and practice of health protective behaviors, such as use of personal protective equipment (PPE). The authors have had similar experience with effective use of engineering controls, such as local exhaust ventilation, following training (Weinstein et al, 2016). As discussed further below, applying CRA approaches to assess workplace safety and health issues will likely lead to new management strategies such as trainings that address risk factors across multiple domains (Fig.…”
Section: Part I: What Are the Current Roles Motivations And Concerns?mentioning
confidence: 99%
“…A systematic review by Robson et al (2010), found that workplace training was effective in increasing worker knowledge of hazards and in development and practice of health protective behaviors, such as use of personal protective equipment (PPE). The authors have had similar experience with effective use of engineering controls, such as local exhaust ventilation, following training (Weinstein et al, 2016). As discussed further below, applying CRA approaches to assess workplace safety and health issues will likely lead to new management strategies such as trainings that address risk factors across multiple domains (Fig.…”
Section: Part I: What Are the Current Roles Motivations And Concerns?mentioning
confidence: 99%